Gender determinism of the effect of placenta cryoextract on the hepatotropic effects of esomeprazole, clarithromycin and metronidazole in chronic liver damage - M. O. Chyzh; I. V. Koshurba; M. M. Marchenko; F. V. Hladkykh; I. V. Belochkina (Сучасні медичні технології)
Current regimens for the eradication of Helicobacter pylori infection include bismuth drugs, proton pump inhibitors, and a combination of 2–3 antibacterial drugs. Uncontrolled use of antibacterial agents as part of eradication schemes increases the risk of developing their unwanted drug reactions, in particular, hepatotoxicity. As a means with potentially hepatoprotective activity, our attention was drawn to placental cryoextract.